Gender-based comparison of factors affecting regular exercise of patients with Non-Insulin Dependent Diabetes Mellitus (NIDDM) based on the 7th Korea National Health and Nutrition Examination Survey (KNHANES). - Ji-Yeon Choi (Public Library of Science (PLoS), 2021)
Objective This study aimed to determine the gender factors that influence regular exercise in patients with non-insulin-dependent diabetes mellitus (NIDDM) in Korea. Methods A total of 1,432 patients with NIDDM were recruited using raw data from the Korea National Health and Nutrition Survey conducted between 2016 and 2018. SAS 9.4 was adopted for data analyses, and the distributional difference was measured with multinomial logistic regression and Rao-Scott x2 statistics to identify the factors that influence the regular physical activities of patients. that the analysis only provides associations. Results Based on general characteristics, health behaviors, and conditions, patients with NIDDM in Korea were less physically active. In addition, patients with higher educational attainment, higher income, and higher subjective health conditions had a higher odds ratio for regular exercise. Meanwhile, the ratio was lower for smokers and those stressed up. Conclusion A professional guide for the initial phase of training and consistent management is required to increase the involvement of patients with NIDDM in regular exercise. Therefore, it is important to maintain their motivation to continue exercising. Rather than providing a universal guideline, it is more important to provide customized programs and management plans which reflect factors that influence their engagement in physical activities, such as individual physical strength, stress level, alcohol consumption, and arthritis.